Slacktivism Strategi Aktivis Mengubah Kebijakan: Studi Kasus Petisi Online Tolak Aturan JHT - Mimi Silvia; Irwansyah Irwansyah (MediaTor (Jurnal Komunikasi), 2022)
Changes in the web have led to the emergence of slacktivism as a social movement with high participation in society at low risk and low cost. Slacktivism relies on the characteristics of Web 1.0, which focuses on hypertext, and Web 2.0, which emphasizes user participation. This research examines the use of Web 1.0 and Web 2.0 by activists as initiators of the online petition Rejection of the 56-year Liquid JHT Rule (Jaminan Hari Tua). This qualitative research uses a case study method by conducting interviews with the initiators of the online petition for the Rejection of the 56-year Liquid JHT Rule. The results of this study found several factors that support the success of slacktivism, including activists' deep understanding of an issue, activists' critical power using Web 1.0 and Web 2.0, issue factors, and storytelling of the issues raised. Activists rely on Web 1.0 as the primary source of information, but Web 2.0 is an essential medium for disseminating information with the power of storytelling regularly. This follows previous research that states that critical people use the Web with different practices than business rhetoric. Slacktivism is a legitimate social movement that can change stakeholder policies with high participation from internet users.